The Communist Party in Canada: A History - Avakumovic, Ivan (McClelland and Stewart, 1975)
The Communist Party in Canada is the first thorough study of a political party whose limited size and position outside the mainstream of politics have not lessened its impact and the interest it has aroused among Canadians for over sixty years. Drawing on Communist sources in several languages, Ivan Avakumovic outlines the party's ups and downs from its origins at the turn of the century through to the present day, traces its connects with the American and Russian Communist parties, and describes its internal organization, its policies and tactics, its attitude to the rest of the left wing and other political parties, to labour groups, police, and the general public. Here is an objective, scholarly description, with appeal for the historian and the general reader. –Publisher's description
OCLC: 1620330
Keywords: Communism Canada; Communist Party of Canada; Communist Party of Canada History; Communist parties Canada; Geschichte; History; Parti communiste canadien Histoire